РОЗРОБЛЕННЯ ЦИФРОВИХ ЗАСОБІВ БАГАТОКАНАЛЬНОГО МОНІТОРИНГУ ПРИСТРОЇВ СИНХРОНІЗАЦІЇ ЧАСУ ЕЛЕКТРОЕНЕРГЕТИЧНИХ SMART GRID СИСТЕМ - Самков, О.В.; Коваль, В.В.; Лисенко, В.П.; Чопик, В.В.; Осінський, О.Л.; Самков, Б.О. (Інститут електродинаміки Національної академії наук України, 2023)
The work presents the development results of the means of a computer-integrated system of multi-channel monitoring of time synchronization devices, which is designed to increase the reliability of digital data of synchronous vector measurements of the power SMART Grid systems. The design documentation was developed, and a prototype of the multi-channel monitoring device was manufactured. A segment of the information digital system for transmitting monitoring data was created using the corporate IP network of the IED of the NAS of Ukraine, Cisco-certified equipment, and multi-channel monitoring devices mounted on a laboratory stand. Experimental studies and testing of the manufactured experimental model of the multi-channel monitoring device on the operating IP network were carried out. It was established that the obtained characteristics of the researched digital means of multi-channel monitoring and the information system of data transmission meet the requirements of the technical assignment. The organizational structure of the multi-channel monitoring system of time synchronization devices is presented, and recommendations for its use in electric power enterprises are developed. Ref. 10, fig. 2.